FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN WADAH STYROFOAM SEBAGAI KEMASAN MAKANAN PADA PENJUAL MAKANAN JAJANAN DI KOTA PONTIANAK TAHUN 2016 - Ela, Ela; Rochmawati, Rochmawati; Selviana, Selviana (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Styrofoam is a syntheticaromatic polymer made from the monomer styrene. The use of improper food containers can result in the migration of monomer styrene into the food so that it can pose a significant risk of diseases such as headache, fatigue, depression, and anemia. The migration caused by the temperature, the duration of use, and the type of food. This study aimed at analyzing the factors related to the use of foam food containers among food-sellers in Kota Pontianak.Using analytic descriptive method and cross sectional design, as many as 52 samples participated in this study.The study revealed that as many as 51.9% food-sellers used Styrofoam as the food containers. There were no correlation of heat resistant, obtainability, affordability and the use of food foam containers.From the findings, the foo-sellers need to pay attention on the packaging feassibility. They are encouraged to find out the health standard of the foam food container as it contains of cmemical substances that easily and quickly switch to food in hot conditions.Keywords : Styrofoam, heat resistant, obtainability, affordability.